Probing strangeness canonical ensemble with K−, ϕ(1020) and Ξ− production in Au+Au collisions at √sNN=3 GeV - Abdallah, Mohamed Samy; Deppner, Ingo Martin; Herrmann, Norbert; Söhngen, Yannick; Weidenkaff, Philipp (Physics letters, 2022)
We report the first multi-differential measurements of strange hadrons of K−, ϕ and Ξ− yields as well as the ratios of ϕ/K− and ϕ/Ξ− in Au+Au collisions at sNN=3 GeV with the STAR experiment fixed target configuration at RHIC. The ϕ mesons and Ξ− hyperons are measured through hadronic decay channels, ϕ→K+K− and Ξ−→Λπ−. Collision centrality and rapidity dependence of the transverse momentum spectra for these strange hadrons are presented. The 4π yields and ratios are compared to thermal model and hadronic transport model predictions. At this collision energy, thermal model with grand canonical ensemble (GCE) under-predicts the ϕ/K− and ϕ/Ξ− ratios while the result of canonical ensemble (CE) calculations reproduce ϕ/K−, with the correlation length rc∼2.7 fm, and ϕ/Ξ−, rc∼4.2 fm, for the 0-10% central collisions. Hadronic transport models including high mass resonance decays could also describe the ratios. While thermal calculations with GCE work well for strangeness production in high energy collisions, the change to CE at 3 GeV implies a rather different medium property at high baryon density.
Im Titel ist das Minuszeichen hochgestellt, "NN" bei sNN tiefgestellt, dabei steht der ganze Ausdruck unter dem Wurzelsymbol
Gesehen am 04.10.2021